Multi-facet Leadership Approach for Organizational Performance in the Evolving Globalized Landscape of the New Millennium Era - Wooi, CHOW, Tong; Samuel ADEDEJI, Babatunji (International Journal of Psychosocial Rehabilitation, 2020)
This paper explores the critical emerging leadership competencies for performance in the new millennium era. Due to the changing leadership landscape, research becomes vital to determine the critical emerging leadership competencies that would contribute to sustainable competitive leadership advantage for 21st-century leaders and organisations. The key findings from the study include the preferred choice of transformational leadership and the relevance of the leadership competency paradigm. Modern leaders need leadership competencies for progressive leadership. Main findings include the key emerging leadership competencies of visioning and strategic thinking, leadership agility, adaptability and change, relationships, and collaboration. Also, the new results emerging from the data were corporate leadership and cross-cultural competence. The research employed the qualitative case study conducted in only one of the public research universities in Malaysia. The data from the interviews with the top leaders of the institution provided the in-depth contextual responses to the interview questions. It is essential to know and adopt the right concept of leadership in concert with the times for progressive leadership development and practice. The study shows the relationship between the expected attributes of an organisational leader, dimensions of transformational leadership, and the emerging leadership competencies. There is a scarce empirical study on organisational leadership employing the emerging leadership competency concept. Also, the conceptual framework of the study has a connection to transformational leadership. Hence, the research of this nature has values. The findings were original contributions to knowledge.This study contributed to theory, practice, context, methodology, and policy.